Effect of stacking sequence on layer hybridization as well as static and dynamic mechanical properties of fiber reinforced composites - Eroglu, Mehmet; Kara, Numan; Yanen, Cenk; Kaman, Mete Onur (Walter de Gruyter Gmbh, 2026)
This study investigates the development and mechanical characterization of hybrid and non-hybrid composite materials reinforced with carbon fiber, basalt fiber, glass fiber, and 304 stainless steel fabric within an epoxy matrix. The aim is to create composites with enhanced tensile strength, flexural strength, and impact resistance for potential applications in blast-resistant structures. Composite laminates were fabricated using a hand lay-up method, followed by curing under pressure to ensure optimal interfacial bonding. Mechanical testing, including tensile, three-point bending, Charpy impact, and low-velocity drop weight tests, was conducted in accordance with ASTM standards. Scanning electron microscopy (SEM) analysis provided insights into fracture mechanisms and delamination behavior. The results show that hybrid composites exhibit inferior static mechanical properties compared to non-hybrid pure carbon, glass and basalt composites, but certain hybrid configurations show significant improvements energy absorption due to the steel mesh. These findings suggest that the strategic combination of different fibers and metallic fabrics can be tailored to meet specific engineering requirements, offering a pathway for designing advanced materials in the aerospace, automotive, and defense industries.
Keywords: hybrid composites; steel mesh wire; tensile; drop test; energy absorption